2019
DOI: 10.36713/epra3760
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Good Corporate Governance, Company Sizes, and Leverage of Tax Avoidance

Abstract: The purpose of this study is to analyze how much influence the board of commissioners, audit committee, institutional ownership, company size and leverage on tax avoidance on food and beverage sector companies listed on the Indonesia Stock Exchange. The factors tested in this study are tax avoidance as the dependent variable while the size of the board of commissioners, audit committee, institutional ownership, firm size and leverage as independent variables. The sample of this study consisted of 15 food and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
1
0
2
Order By: Relevance
“…Perusahaan menggunakan leverage untuk menghasilkan keuntungan lebih besar daripada biaya aset serta sumber dana, sehingga meningkatkan keuntungan pemegang saham. Sebaliknya, leverage juga meningkat variabilitas keuangan (risiko), karena jika perusahaan ternyata mendapatkan keuntungan yang lebih rendah dari biaya tetapnya maka penggunaan leverage akan mengurangi keuntungan pemegang saham (Listyaningsih et al 2019).…”
Section: Leverage Dan Penghindaran Pajakunclassified
See 1 more Smart Citation
“…Perusahaan menggunakan leverage untuk menghasilkan keuntungan lebih besar daripada biaya aset serta sumber dana, sehingga meningkatkan keuntungan pemegang saham. Sebaliknya, leverage juga meningkat variabilitas keuangan (risiko), karena jika perusahaan ternyata mendapatkan keuntungan yang lebih rendah dari biaya tetapnya maka penggunaan leverage akan mengurangi keuntungan pemegang saham (Listyaningsih et al 2019).…”
Section: Leverage Dan Penghindaran Pajakunclassified
“…Ukuran perusahaan merupakan skala atau nilai yang dapat mengklasifikasikan perusahaan ke dalam kategori besar atau kecil berdasarkan total aset, log, ukuran, dan sebagainya. Semakin besar total aset maka semakin besar juga ukuran perusahaan, sehingga memungkinkan perusahaan yang ada untuk melakukan tindakan penghindaran pajak dari setiap transaksi (Listyaningsih et al 2019).…”
Section: Company Size Dan Penghindaran Pajakunclassified
“…The procedure for preparing the financial statements is not just a journal posting process but goes further to the validity of transactions and supporting documents, including transactions related to taxation. Some studies found a negative effect of audit quality on tax avoidance or positive impact [8,9].…”
Section: Introductionmentioning
confidence: 99%